Tunable bimetallic Au–Pd@CeO2 for semihydrogenation of phenylacetylene by ammonia borane. Issue 27 (1st July 2019) - Liu, Yu; Wang, Qishun; Wu, Lanlan; Long, Yan; Li, Jian; Song, Shuyan; Zhang, Hongjie
Abstract : The bimetallic core ceria shell Au–Pd@CeO2 has been successfully fabricated through a one pot autoredox reaction, which shows high activity and selectivity towards the semihydrogenation of phenylacetylene by ammonia borane. Abstract : The fabrication of a bimetallic core and ceria shell nanostructure is considered a promising way to promote catalytic performance and stability. Here, we report an Au–Pd@CeO2 core–shell structure with a tunable Au/Pd ratio through a self-assembly autoredox reaction approach. This process involves the sequence reduction of Au and Pd precursors and then self-assembly of CeO2 nanoparticles to encapsulate the noble metal core. The as-obtained samples exhibit excellent activity and selectivity towards the ammonia borane initiated hydrogenation of phenylacetylene with an enhanced stability owing to the protection from outside CeO2 nanoparticles. Through the construction of an Au–Pd bimetallic structure, an electron modification of Pd due to charge transfer between Au and Pd results in an enhanced catalytic performance. Such a strategy is promising for the synthesis of other bimetallic noble core and ceria shell structures for further applications.